Direitos do homem como pré-requisito para a implantação da democracia e da paz no pensamento de Norberto Bobbio - Reis, Medéia Laís (2022)
This research deals with human rights, democracy and peace, covering Norberto Bobbio's thought and the most relevant factors in his life that motivated him to write on the subject in question. The research goes from his oldest texts to the last writings before his death. Thus, the main bibliographic reference is the book Age of rights, because in it the author compiles his main articles and reflections carried out during his life on the subject. The main objective is to analyze the correlation between the concepts of human rights, democracy and peace, because without human rights protected and recognized, it is not possible to have democracy and without it it is not possible to have peace. Therefore, it is convenient to start the work by analyzing the events that impelled Norberto Bobbio to write about human rights, as a prerequisite for the implementation of democracy and peace. In this way, we seek to answer the problem: how can human rights, democracy and peace be three necessary moments of the same historical movement? Therefore, the present work is organized in three moments, the first one aims to present an analysis of Norberto Bobbio's cultural profile and the main events in his life that motivated him to write about this topic. The second moment aims to explore what human rights are, based on the Universal Declaration of Human Rights of 1948, which became a landmark of universal rights. This declaration is brought to the work, as it is the focus of analysis of the philosopher studied here, who even compares it with the previous declaration, from 1789, entitled Universal Declaration of the Rights of Man and Citizen. Such a historical movement is carried out to demonstrate that the contemporary problem of human rights is not due to the lack of rights and the need to establish new rights, but to the recognition and protection of existing rights. For Bobbio, after the 1948 Declaration, human rights were no longer desirable, as they gained widespread recognition. For the first time in the world, human individuals from all parts of the planet agreed on common rights that must be applied by each and every individual, regardless of nationality, race, creed, religion, culture, economy, politics, among other possible variations. These rights are universal and common and do not compete with other rights. The third moment deals with democracy and peace, emphasizing that together with human rights they make up a historical and political movement. Human individuals living in a democratic society, having their rights guaranteed and protected, will consequently have peace, and this peace does not have war as an alternative, war being the denial of the right, the right in return is the affirmation of peace. A State without rights, in which positive laws do not exist, cannot be democratic and, therefore, will not have peace. Finally, it is understood that Bobbio's contribution on the subject is of paramount importance for understanding a system of universal values, speaking of real plans, seeking the effective protection of rights already declared for human beings of all cultures.